(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
What is Horticulture? Horticulture, from Latin hortus meaning garden and colere meaning to cultivate, focuses on the use of small plots, in contrast to agronomy which involves intensive crop farming and large-scale field crop production of grains and forages or foresty involving forest trees and products derived from them. It deals with garden crops such as ornamental plants grown for their appearance, fruits and vegetable and spices grown for their food value, and medicinal plants.